(untitled) (Czech Journal of International Relations, 1992)
On December 5-6, 1990, an international scientific conference was held in Prague with the theme: Revolutionary changes in the Soviet Union and Eastern and Central Europe and their influence on the orthodox communist regimes in Cuba, the DPRK, and China. The year 1989 went down in history as a period of unexpected revolutions that caused strategic changes in the geopolitical area, which until then was known as the "socialist community" (or "socialist camp", etc.). New political thinking and reconstruction in the Soviet Union caused such an unprecedented tolerance towards Eastern and Central Europe that it allowed democratic forces to overthrow the orthodox communist regimes, either by non-violent means like in Poland, Czechoslovakia and Hungary, or by means of a violent revolution like in Romania completely completed, even irreversible, and their long-term perspective remains problematic to a certain extent, they had and still have a significant influence on orthodox regimes in such countries as Cuba, China, and the DPRK.